The Influence of Training, Development, and Employee Skills on the Performance of SME Employees in Boyolali Regency - Ardian Irawandanu; Kusdiyanto Kusdiyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of training, development, and employee skills on the performance of SME employees in Boyolali Regency. The research employs a quantitative approach using a survey technique, distributing questionnaires to SME owners and employees who have participated in training and development programs. The sample was selected using purposive sampling. Data analysis was conducted using SEM PLS, along with validity, reliability, and significance tests. The results indicate that training does not have a significant effect on employee performance, while employee development and skills have a positive and significant impact. Therefore, SMEs are advised to focus more on structured and sustainable employee development programs and provide opportunities for employees to enhance their skills. Although training does not significantly influence performance, it is important for SMEs to continuously evaluate and improve the quality of training. This study also offers recommendations for future research to explore additional variables and expand the research context.